Studi Literature: Potensi Resveratrol sebagai Efek Immunodulator dalam Pencegahan Penyakit Autoimun - Rachmat Faisal Syamsu; Nurafni Maharani Nawawi; Nur Zahra Noor Khaerani Hazminafni (Universitas Malahayati Lampung, 2025)
ABSTRACT Autoimmune diseases are characterized by the immune system’s failure to distinguish self from non-self, resulting in the immune-mediated destruction of the body’s own tissues. Current treatments largely rely on immunosuppressive and anti-inflammatory drugs, which, despite their effectiveness, are often associated with significant long-term side effects. Consequently, there is a growing need for safer and more effective therapeutic alternatives. Resveratrol, a natural polyphenolic compound predominantly found in the skin of red grapes, has emerged as a promising immunomodulatory agent. This literature review aims to explore the potential of resveratrol in the prevention of autoimmune diseases by analyzing 15 peer-reviewed articles published between 2017 and 2025, sourced from PubMed, NCBI, and Google Scholar. Findings indicate that resveratrol modulates immune function by suppressing the activation of T and B lymphocytes, inhibiting the release of proinflammatory cytokines (such as TNF-α, IL-6, IL-17, and IL-1β), and regulating key molecular pathways including SIRT1, NF-κB, and AMPK. It also enhances the population of regulatory T cells (Tregs) and exerts antioxidant effects by neutralizing reactive oxygen species (ROS) and upregulating antioxidant enzyme activity. Clinical studies have reported favorable outcomes in patients with autoimmune conditions such as rheumatoid arthritis, ulcerative colitis, systemic lupus erythematosus, and multiple sclerosis. Despite these encouraging results, further investigations are required to determine optimal dosing strategies and evaluate long-term safety profiles. Overall, resveratrol demonstrates significant potential as a natural immunomodulatory agent in the prevention and management of autoimmune diseases. Keywords: Resveratrol, Immunomodulation, Autoimmune Disease, Cytokines, Inflammation. ABSTRAK Penyakit autoimun merupakan kondisi di mana sistem imun kehilangan kemampuan untuk mengenali “diri” sendiri dan menyerang jaringan tubuh, menyebabkan kerusakan sistemik maupun organ-spesifik. Terapi konvensional seperti obat imunosupresif dan antiinflamasi seringkali menimbulkan efek samping jangka panjang, sehingga dibutuhkan alternatif terapi yang lebih aman. Resveratrol, senyawa polifenol alami yang ditemukan dalam kulit anggur merah, telah menunjukkan potensi sebagai agen imunomodulator. Studi ini bertujuan untuk menelaah potensi resveratrol dalam pencegahan penyakit autoimun berdasarkan tinjauan terhadap 15 artikel ilmiah dari database PubMed, NCBI, dan Google Scholar (2017–2025). Hasil review menunjukkan bahwa resveratrol mampu menekan aktivasi sel T dan B, menghambat pelepasan sitokin proinflamasi (seperti TNF-α, IL-6, IL-17, IL-1β), mengaktivasi jalur molekuler seperti SIRT1, NF-κB, AMPK, serta meningkatkan populasi sel T regulator (Treg). Selain itu, resveratrol juga bertindak sebagai antioksidan yang menetralkan ROS dan meningkatkan aktivitas enzim antioksidan. Dalam konteks klinis, resveratrol menunjukkan manfaat pada pasien rheumatoid arthritis, ulcerative colitis, lupus, multiple sclerosis, dan penyakit autoimun lainnya. Meskipun hasil studi menjanjikan, dibutuhkan penelitian lebih lanjut untuk menetapkan dosis optimal dan keamanan jangka panjang. Resveratrol berpotensi menjadi terapi imunomodulator alami yang menjanjikan dalam pencegahan penyakit autoimun. Kata Kunci: Resveratrol, Imunomodulator, Penyakit Autoimun, Sitokin, Antiinflamasi.